2020
DOI: 10.1186/s12879-020-05383-y
|View full text |Cite
|
Sign up to set email alerts
|

Differential diagnosis for suspected cases of coronavirus disease 2019: a retrospective study

Abstract: Background Since December 2019, the coronavirus disease 2019 (COVID-19) has infected more than 12,322,000 people and killed over 556,000 people worldwide. However, Differential diagnosis remains difficult for suspected cases of COVID-19 and need to be improved to reduce misdiagnosis. Methods Sixty-eight cases of suspected COVID-19 treated in Wenzhou Central Hospital from January 21 to February 20, 2020 were divided into confirmed and COVID-19-negative groups based on the results of real-time reverse transcri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 16 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…Multiplex PCR tests have recently been reported to be useful for differentiating severe COVID‐19 from severe MPP that require antimicrobial therapy with or without anticoagulation treatment. 5 Multiplex PCR tests and the 16S rRNA gene analysis using bronchoalveolar lavage fluid were useful for confirming M. pneumoniae in our patient, which allowed us to initiate appropriate antimicrobial therapy.…”
Section: Discussionmentioning
confidence: 74%
“…Multiplex PCR tests have recently been reported to be useful for differentiating severe COVID‐19 from severe MPP that require antimicrobial therapy with or without anticoagulation treatment. 5 Multiplex PCR tests and the 16S rRNA gene analysis using bronchoalveolar lavage fluid were useful for confirming M. pneumoniae in our patient, which allowed us to initiate appropriate antimicrobial therapy.…”
Section: Discussionmentioning
confidence: 74%
“…Performing multiplex PCR testing through sputum or throat swabs helps to distinguish different pathogens such as influenza A virus, influenza B virus, Adenovirus, RSV, Chlamydia pneumoniae and Mycoplasma pneumoniae from COVID-19 infection [ 14 ]. However, this method may be related to multiple factors such as quality of sampling, specimen preservation, and varying concentration of nasopharyngeal at different stages of the disease [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, low WBC counts had an inverse relation with cancer risk in the present study. Recent studies have demonstrated that WBC counts are inversely correlated with fever and severity from coronavirus disease 2019 (COVID-19) infection in the chest damage showing by imaging analysis, including ground-glass opacities and multiple patchy shadows [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%